A new species of the genus Leptobrachium (Anura: Megophryidae) from the Gaoligongshan Mountain Range, China - Yang, Jian-Huan; Wang, Ying-Yong; Chan, Bosco Pui-Lok (Zootaxa, 2016)
We describe a new species of the genus Leptobrachium from the Gaoligongshan Mountain Range, Yunnan Province of China based on molecular and morphological evidences. The new species, Leptobrachium tengchongense sp. nov., can be distinguished from its congeners by a combination of the following characters: (1) relatively small size (adult males SVL 41.7–51.5 mm); (2) head width slightly larger than head length; (3) tympanum indistinct; (4) two palmar tubercles oval and distinct, inner one larger than outer one; (5) sexually active males without spines on the upper lip; (6) dorsal skin smooth with distinct network of ridges; (7) dorsum pinkish grey and scattered with irregular black markings; (8) venter dark purplish-gray with numerous small white spots on tubercles, solid white chest; (9) iris bicolored, upper one-third light blue, lower two-third dark brown. With the description of the new species, the number of Leptobrachium species currently known from China adds up to ten.